(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The study reviews key findings on the impact of banking growth and innovation on economic development, particularly focusing on Asian economies where the financial sector is less developed. Using secondary data, it expands the scope of analysis to more specific elements of development. While banking innovation’s theoretical effects are vast, empirical findings are often less clear, as they focus on specific businesses and channels. The study highlights the importance of understanding the current state of the financial sector when assessing its role in growth. Artificial intelligence (AI) and Big Data are increasingly used in economic forecasting, offering predictive and decision-making capabilities. The research concludes that greater economic freedom, especially in cross-border financial markets, does not always benefit companies. International financial freedom can hinder development, while domestic financial freedom may support it. As weaker banks struggle to finance startups, the study suggests that financial freedom may yield varied results for economic and business growth. In regions with underdeveloped financial markets, like Asia, banks play a crucial role in fostering growth. The article emphasizes the importance of financial technology in shaping these outcomes.